Analyzing Potential Use of 3D Machine Vision and AI Algorithms at Robotic Workstations - Jarosław PANASIUK; Jarosław PANASIUK (Analiza możliwości wykorzystania wizji maszynowej 3D i algorytmów AI na stanowiskach zrobotyzowanych, 2025)
The following article presents an analysis concerned with the potential use of vision and machine learning solutions implemented at automated workstations with industrial robots. Aspects related to various elements of such stations and theoretical foundations have been analyzed, and examples of equipment and program components have been given to open up new options related to industrial robotics, trajectory planning, collision avoidance, and safety.
Keywords: Algorytmy AI na stanowiskach zrobotyzowanych; Algorytmy AI na stanowiskach zrobotyzowanych